Analisis Sitem Informasi Akuntansi Pembelian Obat-Obatan terhadap Pengendalian Internal Pembelian Obat-Obatan pada Klinik Pratama Rawat Inap Ridos - Aprilia Gloria Br Tarigan; Mulatua Pandapotan Silalahi; Rahel Junita Nainggolan (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
This study aims to explore the benefits of the accounting information system used in the drug purchasing process at the Ridos Inpatient Pratama Clinic, as well as to disseminate the internal control system used in the system, the accounting information system in drug purchases functions by managing purchase transaction data, recording, reporting drugs and internal control of drug purchases that control and control drug purchases. Data collection was carried out using a qualitative descriptive approach method, namely, interviews, observations, and collecting supporting evidence. From the results of this study, the accounting information system implemented is quite good. However, the system used does not optimally support internal control, strengthening internal policies and staff training is needed to improve the effectiveness of internal control of the drug purchase accounting information system.